Nutritional Management With a Casein-Based Extensively Hydrolysed Formula in Infants With Clinical Manifestations of Non-IgE-Mediated CMPA Enteropathies and Constipation - Sekkidou, Mikaela; Muhardi, Leilani; Constantinou, Constantina; Kudla, Urszula; Vandenplas, Yvan; Nicolaou, Nicolaos (Frontiers in Allergy, 2021)
Background: The majority of mixed-fed infants with non-IgE-mediated cow's milk protein allergy (CMPA) enteropathies are managed with an extensively hydrolysed cow's milk based infant formula (eHF). Given the high variability in peptide distribution of available eHFs, it is important to understand the suitability of a specific product in the management of distinct phenotypes. Objective: To assess the symptom resolution of various phenotypes of clinical manifestations of CMPA enteropathies and constipation managed by a casein-based eHF. Methods: The data of 20 full-term infants (n = 15 with non-IgE-mediated CMPA and n = 5 with constipation) attending a paediatric allergy clinic in Cyprus and managed with a casein-based eHF were retrospectively analysed. Results: Based on the clinical symptoms and history, infants were classified into the following phenotypes: (a) 11/15 (73.3%) FPIAP, (b) 3/15 (20%) FPIES, and (c) 1/15 (6.7%) severe diarrhoea. Overall, 14 (93.3%) patients were successfully managed with the casein-based eHF and 1 (6.7%) required an AAF. This formula was effective in 91% of patients with FPIAP, in 100% with FPIES and with diarrhoea. Three (60%) patients with constipation responded to the eHF. Conclusion: This case-series report supports the efficacy of a particular casein-based eHF for the nutritional management of non-IgE mediated CMPA enteropathies.